Empenhando-se em promover um ensino significativo do brinquedo terapêutico, almejando a qualidade do cuidado à criança: vivência do docente de graduação em enfermagem - Maia, Edmara Bazoni Soares [UNIFESP] (2016)
This qualitative study aimed to understand the teacher's experience in the teaching process of Therapeutic Play in undergraduate nursing courses and to build a representative Theoretical Model of this experience. The theoretical framework was Symbolic Interactionism and the methodological, Grounded Theory. The project was approved by the Ethics Committee of the Federal University of São Paulo under No. 394,373/13. It took place at disciplines dealing with the theoretical and practical teaching of Pediatric Nursing in undergraduate nursing courses in institutions in which the teacher interacts with the teaching of Therapeutic Play, other teachers, students and people involved in the teaching-learning process, such as the child's family and care professionals. Study participants were 18 teachers and three nurses involved in the teaching of these subjects, and the number of participants was determined by theoretical sampling process. Data were collected by participant observation and a semi-structured interview started with the guiding question: How do you perceive the teaching of Therapeutic Play in Undergraduate Nursing Courses? Data analysis was conducted concomitantly with their collection, making it possible to understand that the teacher's experience in the teaching process in undergraduate nursing courses is dynamic as teacher's actions and interactions are subject to frequent changes due to the need to align the actions of the players involved. It is composed of two phenomena, the first, Mobilizing oneself for the teaching of Therapeutic Play (TP) to become a reality in the undergraduate nursing course, reveals all the movements undertaken by the teacher, seeking to ensure that the teaching of Therapeutic Play can become a reality while interacting with concerns and questions related to the reality of teaching. This, in turn, results in the need to know this reality and mobilizes the teacher to prepare himself/herself to teach the Therapeutic Play and to implement it. Throughout the process, at each phase of the experiment, the teacher hopes that the teaching of Therapeutic Play will be able to provide students with information and knowledge about quality child care. The second phenomenon, Worrying about offering the student meaningful learning shows the teacher's commitment to turn the planned actions into reality. The teacher seeks to provide students with opportunities to interact with both theoretical and active teaching and experience the Therapeutic Play in clinical practice so that students can be touched by the experience thus broadening their perspective concerning the importance of this topic. It reveals that although the teacher needs to make an effort to overcome difficulties, he/she is strengthened by the interactions and positive changes that this teaching has on the academic environment. Therefore, the teacher is hopeful, envisioning a future in which the child will be provided with high quality care, which includes the systematic use of the Therapeutic Play. The integration of these categories allowed the identification of the core category STRIVING TO PROMOTE A MEANINGFUL TEACHING OF THE THERAPEUTIC PLAY, AIMING AT THE QUALITY CHILD CARE and the construction of a representative theoretical model of this experience, which proved to be the essence of what it means for the teacher to experience the teaching process of the Therapeutic Play in undergraduate nursing courses